The long-term predictive accuracy of the short synacthen (corticotropin) stimulation test for assessment of the hypothalamic-pituitary-adrenal axis. - Agha, A; Tomlinson, J; Clark, P; Holder, G; Stewart, P (2006)
CONTEXT: The high-dose short Synacthen (corticotropin) test (SST) is widely used to investigate suspected secondary adrenal insufficiency, but concern remains about falsely reassuring results. OBJECTIVE: Our objective was to evaluate the long-term safety of the SST. METHOD: We retrospectively evaluated the clinical outcome in 178 patients who achieved 30-min cortisol values in the lowest 15th percentile of normal healthy responses. Thirty patients were later excluded because of missing case notes (20 patients) or unsubstantiated pituitary pathology (10 patients). The remaining 148 patients were divided into two groups: group 1, patients with cortisol response between the 5th and 15th percentiles of normal response (551-635 nmol/liter, 98 patients); and group 2, patients with borderline response between the 2.5th and 5th percentiles (510-550 nmol/liter, 50 patients). Patients did not receive routine glucocorticoid therapy, but those in group 2 were advised to take hydrocortisone in case of intercurrent illness. RESULTS: The median follow-up period from the initial SST was 4.2 yr (range, 4 months to 7 yr). A total of 137 patients showed no clinical or biochemical evidence of adrenal insufficiency during follow-up. Of the remaining 11 patients, seven became hypoadrenal after subsequent pituitary surgery or radiotherapy, one patient in group 1 developed adrenal insufficiency at 2 yr, and one patient in group 2 developed adrenal insufficiency at 6 months. The other two patients who were in group 2 had clinical diagnostic uncertainty. CONCLUSION: The high-dose SST is safe for the purpose of excluding clinically significant secondary adrenal insufficiency and is indicated as the first line of investigation for this purpose.